2023
DOI: 10.31234/osf.io/8r9p7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Objecting to consensual experiments even while approving of nonconsensual imposition of the policies they contain

Abstract: In previous survey studies using decision-making vignettes in which respondents rated and ranked the appropriateness of universally implementing one intervention for all relevant people (A), universally implementing another intervention (B), or conducting an experiment (or A/B test) to compare these interventions before implementing the superior one, we have found that people are often averse to the A/B test, even when they approve of implementing either of the interventions the experiment contains (Meyer et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In 8 of 9 vignettes, more than 25% of participants ranked the A/B test as the worst option. Moreover, and contrary to MEM’s claim—in both their original paper and their reply—that people often prefer experiments, in none of their vignettes (or ours) was there significant experiment appreciation [when correctly defined as the inverse of EA, i.e., preferring the A/B test to the highest ( 8 , 9 )—not the lowest ( 1 )—rated policy]. Indeed, in several vignettes, significantly more participants were experiment-averse than experiment-appreciative.…”
contrasting
confidence: 83%
See 3 more Smart Citations
“…In 8 of 9 vignettes, more than 25% of participants ranked the A/B test as the worst option. Moreover, and contrary to MEM’s claim—in both their original paper and their reply—that people often prefer experiments, in none of their vignettes (or ours) was there significant experiment appreciation [when correctly defined as the inverse of EA, i.e., preferring the A/B test to the highest ( 8 , 9 )—not the lowest ( 1 )—rated policy]. Indeed, in several vignettes, significantly more participants were experiment-averse than experiment-appreciative.…”
contrasting
confidence: 83%
“…Using this definition, a person shows experiment “preference” if they rate the A/B test higher than they rate their least-preferred policy. We believe that such a “preference” is not meaningful and instead calculate experiment appreciation which is defined as the difference between the rating of the A/B test and the rating of the highest-rated policy ( 8 , 9 ). Using this definition, a person shows experiment appreciation when they like the A/B test more than their favorite policy, a characteristic that we find meaningful.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 5 pre-registered the aim to answer whether EA continues to emerge when respondents have complete information about all treatment options and found that it does. Also, while a new preprint ( 11 ) manipulated consent, it found that decisions for consensual experiments continued to be evaluated as relatively less appropriate. Importantly, given VHWCM’s classification, all our between-subject designs were in fact nonconsensual ( Table 1 ), yet they did not reveal relatively lower appropriateness-ratings.…”
mentioning
confidence: 99%